Residual stress and adhesion of thermal spray coatings: Microscopic view by solidification and crystallisation analysis in the epitaxial CoNiCrAlY single splat. (5th September 2018) - Fanicchia, F.; Maeder, X.; Ast, J.; Taylor, A.A.; Guo, Y.; Polyakov, M.N.; Michler, J.; Axinte, D.A.
Abstract: A new approach is proposed to achieve an in-depth understanding of crystallisation, residual stress and adhesion in epitaxial splats obtained by Combustion Flame Spray. Modelling of the fundamental process mechanisms is achieved with the help of experimental observations providing details with a sub-micrometre spatial resolution. At this scope, High Angular Resolution Electron Backscatter Diffraction and Transmission Electron Microscopy analysis are employed to provide insights into crystallisation and residual stress levels, while FIB-milled microcantilever beam bending is used for fracture strength measurements in the case of single splats. A comparison to fully-developed coatings is achieved by employing the X-ray Diffraction sin 2 ψ technique and pull-off methods for residual stress and fracture strength, respectively. The methodology is applied to metallic CoNiCrAlY material sprayed onto a Ni-based superalloy substrate. The establishment of different crystallisation regions: epitaxial and polycrystalline, is the result of variations in the heat flux direction at the solidification front. Significant dislocation density is also reported, indicating the relevance of impact dynamics and plastic deformation mechanisms. The comparison with fully-developed coatings suggests a reduction in inter-splat bonding at splat overlapping. Graphical Abstract: Highlights: Crystallisation, residual stress and adhesion are characterised in thermally sprayed CoNiCrAlY single splats. HR-EBSD, TEM, FIB-milled cantilever beam bending and sin 2 Ψ and pull-off method have been used. A dual epitaxial/polycrystalline structure and a gradient in fracture strength is observed in the single splats. Lower residual stress/adhesion in coatings vs single splat is linked to lower intersplat chemical-mechanical interaction.